Some Aspects of Neonatal Convulsions - S. K. Hendarto; Sofjan Ismael; S. M. Lumbantobing; S. Lazuardi (Indonesian Pediatric Society, 1974)
The purpose of this paper is to review and evaluaute the clinical dataon incidence, sex, body-weight, morbidity and mortality and the possible etiology of convulsions occurring in the neonatal period (i.e. the first 30 days of life) and to study the outcome in follow up examination at the age of more than 6 months. The age of 6 months is taken as a limit because previous experiences and those of other authors (Billing, 1964) have shown that only after the age of 6 months neurological and mental disorders remain evident and permanent.